2019
DOI: 10.1038/s41598-019-50664-5
|View full text |Cite
|
Sign up to set email alerts
|

Manganese protects wheat from the mycotoxin zearalenone and its derivatives

Abstract: Searching for factors that reduce zearalenone (ZEN) toxicity is an important challenge in wheat production, considering that this crop is a basic dietary ingredient. ZEN, absorbed by cells, is metabolized into α-zearalenol and α-zearalanol, and this study focused on the function of manganese ions as potential protectants against the mycotoxins. Stress effects were invoked by an application of 30 µM ZEN and its derivatives. Manganese ions were applied at 100 µM, not stress-inducing concentration. Importance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…A typical mode of action of MDTs involves either forming bulky non-absorbable complexes with mycotoxins in the gastrointestinal tract, hence reducing their oral bioavailability, or promoting their degradation into non-toxic metabolites by bio-transforming agents, such as bacteria or enzymes 1 , 15 , 16 . Adsorbents capture mycotoxins which are delivered through the gastrointestinal tract of the animals with their feed, and the mycotoxin-MDT complex is eliminated with feces thus minimizing the absorption in the blood stream 17 .…”
Section: Introductionmentioning
confidence: 99%
“…A typical mode of action of MDTs involves either forming bulky non-absorbable complexes with mycotoxins in the gastrointestinal tract, hence reducing their oral bioavailability, or promoting their degradation into non-toxic metabolites by bio-transforming agents, such as bacteria or enzymes 1 , 15 , 16 . Adsorbents capture mycotoxins which are delivered through the gastrointestinal tract of the animals with their feed, and the mycotoxin-MDT complex is eliminated with feces thus minimizing the absorption in the blood stream 17 .…”
Section: Introductionmentioning
confidence: 99%
“…The modi cations in the structure of chloroplasts in cereal leaves after direct treatment by ZEN were observed by Kornaś et al [13]. These changes could have been a consequence of ZEN damage of chloroplast membranes resulting from ROS interactions with lipids and/or changes in membranes hydrophilic/hydrophobic structure associated with location of this toxin [14]. The speci c organization of chloroplast membranes containing signi cant amounts of galactolipid fractions (MGDG and DGDG) can provide an environment in which ROS and free electrons may be trapped at sugar groups of these lipids creating long-lived radicals [5].…”
Section: Introductionmentioning
confidence: 85%
“…Manganese presence is indispensable to maintain the redox balance and electron transfer reactions, which is why it plays a valid role in the regulation of excess ROS generation under stress (Maathius and Diatloff 2013). It is suggested that exogenous application of Mn ions limited damage to plant cells by improving antioxidant defense systems, ion homeostasis and diminishing toxic changes in lipid peroxidation, particularly under metal stress conditions (Rahmann et al 2016;Sebastian and Prasad 2015;Gzyl-Malcher et al 2019). However, too high concentration of Mn, above the optimal content in cells (specific for plant cultivars), may induce destructive effects in plant tissues by initiating stress reactions.…”
Section: Introductionmentioning
confidence: 99%